Pneumoconiosis - Report on a patient with pneumoconiosis - Gonzáles Olaechea, Max (1936)
DFF, 32, born in Llata​​, Huamalíes Province, Huánuco. Heredity, his parents died when he was very young, so it ignores the disease which caused his death; has three brothers who are healthy; He is married and has four children who are healthy. His wife has not had abortions. Personal history, denies having diseases, says he was healthy until the first symptoms of the disease that were presented. Only has suffered a trauma in your mouth when trying to open a blade; injury that cost him the two lower central incisors, which has replaced with artificial. No uses of coca, snuff or smoke or drink alcohol usually. Denies having canker or other venereal disease.